Filozoficzne trudności teorii interesariuszy - Soin, Maciej (Annales. Etyka w Życiu Gospodarczym, 2016)
Philosophical difficulties of stakeholder theory – which plays an important role inCSR and business ethics – are connected first of all with questions of its status andjustification. What sense does stakeholder theory have: descriptive, instrumental ornormative? And if normative, why then should executives worry about multiplestakeholder demands?It is well known that Freeman, one of the most important authors of stakeholdertheory, deliberately disregarded these problems. In philosophical questions he invokedRorty’s pragmatism, which in his opinion effectively undermined the “positivistic”dichotomy between facts and values, science and ethics, and enabled stakeholdertheory to be understood at the same time as both descriptive and normative.The article presents some difficulties connected with this view, focusing on itsdubious assumptions and unfavourable consequences. To the assumptions belongsa false dilemma taken from Rorty, which states that knowledge follows either a ruleof representation or a rule of solidarity. One of the unfavourable consequences isthe conclusion that stakeholder theory may be true only if its followers are able toforce the stakeholders to accept its truthfulness.The main thesis of the article says that, as a result of pragmatic justification,stakeholder theory became a sort of arbitrary narration, which is unable to deal withits (empirical) misuses. However, a return to a more traditional view on facts andvalues enables us to appreciate the descriptive advantages of the theory and to identifydifficulties connected with its normative layer. From this point of view, theattempt at a pragmatic interpretation of stakeholder theory was a misunderstandingthat should be withdrawn from circulation.